In-situ imaging of inter- and intra-laminar damage in open-hole tension tests of carbon fibre-reinforced composites. (15th July 2020) - Oz, Fatih E.; Mehdikhani, Mahoor; Ersoy, Nuri; Lomov, Stepan V.
Abstract: This paper investigates damage progression during Open-Hole Tension (OHT) test of carbon fibre-reinforced composites with different Quasi-Isotropic (QI) layups. Digital Image Correlation (DIC) and in-situ edge microscopy are utilized simultaneously to detect damage on the specimen's surface and in the inner plies, respectively. It is found that damage does not always initiate in the 90° plies, but also in the surface 45° plies, depending on the orientation of the adjacent ply. DIC resulting strain field on the surface does not necessarily have the same butterfly-shape concentration around the hole, in all layups. Some laminates show large free edge delaminations at 45°/90° interfaces. This study adds in-situ evidences to the existing data on damage during OHT test of QI laminates, providing quantitative and comparative information on different damage modes, and reveals new features of the damage phenomena.